2020
DOI: 10.1136/annrheumdis-2020-eular.1189
|View full text |Cite
|
Sign up to set email alerts
|

Op0035 examination of Interstitial Lung Disease in Patients With Rheumatoid Arthritis – Prevalence, Time to Onset, and Clinical Characteristics

Abstract: Background:Interstitial lung disease (ILD) is a known extraarticular manifestation of rheumatoid arthritis (RA). Previous studies have shown variability in the prevalence of RA-ILD, as well as clinical characteristics and risk factors of RA-ILD.Objectives:To evaluate the prevalence and time to onset of ILD and compare the clinical characteristics between RA patients (pts) with or without ILD using a large US electronic medical record (EMR)-based dataset.Methods:Pts with an initial RA diagnosis (ICD-9-CM code: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Meanwhile, alternative tools such as PFTs and chest radiography are used for ILD screening. Spirometry is known to exhibit poor sensitivity in diagnosing ILD, a result consistent with our findings 13–32 . Surprisingly, DLCO sensitivity was also poor in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, alternative tools such as PFTs and chest radiography are used for ILD screening. Spirometry is known to exhibit poor sensitivity in diagnosing ILD, a result consistent with our findings 13–32 . Surprisingly, DLCO sensitivity was also poor in our study.…”
Section: Discussionsupporting
confidence: 91%
“…As anticipated, the prevalence of ILD in patients with RA varies based on the study population from which data is derived. Retrospective studies that explored large administrative databases report a prevalence of 2.2%–4.1% 26–28 . Conversely, in studies that systematically screened RA patients for ILD with HRCT, some of them exclusively in patients without respiratory symptoms, the reported prevalence of ILD was 19%–42% 2,4,10 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a retrospective, single-center study noted that 17% of patients with RA-ILD were diagnosed with ILD and RA within the same year [25 && ]. Recently presented data from the Discus JointMan database of incident RA found that 47% of RA-ILD cases developed within 2 years of the onset of articular RA [35].…”
Section: Ild In Early Ramentioning
confidence: 99%
“…ABG, arterial blood gas; ACPA, anti-citrullinated protein antibodies; BAL, bronchoalveolar lavage; CXR, chest radiograph; HRCT, high resolution computed tomography; ILD, interstitial lung disease; n/a, not available; PFTs, pulmonary function tests; RA, rheumatoid arthritis 35…”
mentioning
confidence: 99%
“…ИЗЛ, ассоциированное с РА (РА-ИЗЛ), является серьезным системным проявлением РА, которое связано с высокой смертностью [6][7][8]. Распространенность ИЗЛ при РА составляет 3-4% [6,9]. 26% таких больных имеют прогрессирующий фенотип ИЗЛ [10].…”
unclassified